2006
DOI: 10.1001/jama.295.21.2492
|View full text |Cite
|
Sign up to set email alerts
|

Race, Breast Cancer Subtypes, and Survival in the Carolina Breast Cancer Study

Abstract: Basal-like breast tumors occurred at a higher prevalence among premenopausal African American patients compared with postmenopausal African American and non-African American patients in this population-based study. A higher prevalence of basal-like breast tumors and a lower prevalence of luminal A tumors could contribute to the poor prognosis of young African American women with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

274
3,067
49
93

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,343 publications
(3,529 citation statements)
references
References 45 publications
274
3,067
49
93
Order By: Relevance
“…These findings support the existence of distinct genetic pathways of tumor evolution, common to sporadic and FBC, which underlie the pathogenesis of the different breast tumor subtypes and may explain their distinct biological behavior. Furthermore, we would postulate that gene-expression profiling, clinical presentation and response to therapy also differ in the five FBC IHC subtypes, as already reported in SBC subtypes (Perou et al, 2000;Sorlie et al, 2001Sorlie et al, , 2003Carey et al, 2006;Hu et al, 2006). Taking into account these differences, the BC subtypes should be studied as distinct entities to better describe their features, as has been done for basal-like tumors Yehiely et al, 2006;VincentSalomon et al, 2007).…”
Section: Resultsmentioning
confidence: 54%
“…These findings support the existence of distinct genetic pathways of tumor evolution, common to sporadic and FBC, which underlie the pathogenesis of the different breast tumor subtypes and may explain their distinct biological behavior. Furthermore, we would postulate that gene-expression profiling, clinical presentation and response to therapy also differ in the five FBC IHC subtypes, as already reported in SBC subtypes (Perou et al, 2000;Sorlie et al, 2001Sorlie et al, , 2003Carey et al, 2006;Hu et al, 2006). Taking into account these differences, the BC subtypes should be studied as distinct entities to better describe their features, as has been done for basal-like tumors Yehiely et al, 2006;VincentSalomon et al, 2007).…”
Section: Resultsmentioning
confidence: 54%
“…17,18 Immunohistochemical marker panels that have been proposed to define basal-like breast cancers include: (1) lack of ER, PR, and HER2 expression ('triple-negative' immunophenotype); (2) expression of one or more high-molecular-weight/ basal cytokeratins (CK5/6, CK14, and CK17); (3) lack of expression of ER and HER2 in conjunction with expression of CK5/6 and/or epidermal growth factor receptor (EGFR); 17 and (4) lack of expression of ER, PR, and HER2 in conjunction with expression of CK5/6 and/or EGFR. 19 Despite the different definitions for basal-like breast cancers, it has been demonstrated that these tumors have distinctive clinical presentations, 20 histological features, 18,21 response to chemotherapy, [22][23][24][25][26][27][28] sites of distant relapse, and outcome. 7,9,[29][30][31] In brief, basal-like tumors comprise a heterogeneous group that accounts for up to 15% of all breast cancers, affect younger patients, are more prevalent in African-American women, and often present as interval cancers.…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%
“…Recently, cDNA microarrays of 496 genes of breast cancer tissue identified different prognostic subgroups based on differences in gene expression profiles [22][23][24]. This prognostic subgroup classification of breast cancers seems closely, but not completely, related to the immunohistochemical (IHC) classification of tumors according to their combined expression of hormone receptors and HER-2 [22,25,26]. The partial inconsistency between IHC ''phenotype'' and microarray ''genotype'' is not fully understood and might be partially related to technical issues of receptor determination.…”
Section: Introductionmentioning
confidence: 99%